Proposal for Novel Supercontinuum Generated Photonic Crystal Fiber with High-Power for Ultrahigh-Resolution Optical Coherence Tomography - Begum, Feroza; Kalam Azad, Abul; Abas, Emeroylariffion; Zou, Nianyu (International Journal of Engineering and Technology, 2018)
We represent a novel photonic crystal fiber with high nonlinearity for optical coherence tomography application. The proposed highly nonlinear photonic crystal fibers different properties are computed based on finite difference method. Ultraflattened dispersion, small chromatic dispersion slope, large nonlinear coefficients, and very small confinement loss property are obtained for this designed highly nonlinear photonic crystal fiber. Moreover, the high power wideband super continuum spectrum and high longitudinal resolution of living tissue are achieved. Longitudinal resolution of living tissue is achieved 1.3 Î¼m at center wavelengths 1.1 Î¼m as well as 1.0 Î¼m at center wavelengths 1.31 Î¼m by applying picosecond pulse. Furthermore, the output power of 64.0 W at 1.1 Î¼m center wavelength and 67 W at 1.31 Î¼m center wavelength is demonstrated.Â